2020
DOI: 10.1080/17437199.2020.1846580
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy for stress reduction: a systematic review and meta-analysis

Abstract: Music therapy is increasingly being used as an intervention for stress reduction in both medical and mental healthcare settings. Music therapy is characterized by personally tailored music interventions initiated by a trained and qualified music therapist, which distinguishes music therapy from other music interventions, such as 'music medicine', which concerns mainly music listening interventions offered by healthcare professionals. To summarize the growing body of empirical research on music therapy, a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(142 citation statements)
references
References 163 publications
6
123
0
13
Order By: Relevance
“…Overall, the results provided insights into the role and function of the specific and joint factors in CATs such as embodiment, concretization, symbolism, and metaphors. The results also identified mixed therapeutic factors (Koch, 2014;Wiedenhofer and Koch, 2017;De Witte et al, 2020b), involving the reinforcement of common psychotherapy factors. However, these instances are also connected to intra-and inter-artistic factors within and between each discipline.…”
Section: Domains Of Therapeutic Factors Unique To Cats Researchmentioning
confidence: 94%
See 2 more Smart Citations
“…Overall, the results provided insights into the role and function of the specific and joint factors in CATs such as embodiment, concretization, symbolism, and metaphors. The results also identified mixed therapeutic factors (Koch, 2014;Wiedenhofer and Koch, 2017;De Witte et al, 2020b), involving the reinforcement of common psychotherapy factors. However, these instances are also connected to intra-and inter-artistic factors within and between each discipline.…”
Section: Domains Of Therapeutic Factors Unique To Cats Researchmentioning
confidence: 94%
“…Although the growing number of systematic reviews and meta-analyses of the CATs reflect the increase in individual studies examining the effects of CATs on psychological and physiological outcomes (e.g., Koch et al, 2019 ; De Witte et al, 2020b ), little is known about which change factors of the CATs lead to or impact certain health outcomes. To better understand the CATs-related factors leading to therapeutic change in both physiological and psychological outcomes, we conducted a scoping review of published empirical studies to contribute to disseminating the existing evidence and guide future research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the meta-analysis also showed that music therapy was effective in reducing stress and there were no significant side effects (38). Another advantage of music therapy is that it is a non-drug treatment that is safe, easy to apply and economical so that it can relieve pain, anxiety and depression in post-CABG surgery patients (37).…”
Section: Sensory Therapiesmentioning
confidence: 93%
“…8 – 12 Music has been shown to reduce anxiety, fear, depression, and stress. 13 In addition, music has been shown to increase feelings of happiness and well-being. 14 …”
mentioning
confidence: 99%